Association Between Rotating Night Shift Work and Risk of Coronary Heart Disease Among Women - Vetter, Céline; Devore, Elizabeth E; Wegrzyn, Lani R; Massa, Jennifer; Speizer, Frank E; Kawachi, Ichiro; Rosner, Bernard; Stampfer, Meir J; Schernhammer, Eva S (JAMA : the journal of the American Medical Association, 2016)
Prospective studies linking shift work to coronary heart disease (CHD) have been inconsistent and limited by short follow-up. To determine whether rotating night shift work is associated with CHD risk. Prospective cohort study of 189,158 initially healthy women followed up over 24 years in the Nurses' Health Studies (NHS [1988-2012]: N = 73,623 and NHS2 [1989-2013]: N = 115,535). Lifetime history of rotating night shift work (≥3 night shifts per month in addition to day and evening shifts) at baseline (updated every 2 to 4 years in the NHS2). Incident CHD; ie, nonfatal myocardial infarction, CHD death, angiogram-confirmed angina pectoris, coronary artery bypass graft surgery, stents, and angioplasty. During follow-up, 7303 incident CHD cases occurred in the NHS (mean age at baseline, 54.5 years) and 3519 in the NHS2 (mean age, 34.8 years). In multivariable-adjusted Cox proportional hazards models, increasing years of baseline rotating night shift work was associated with significantly higher CHD risk in both cohorts. In the NHS, the association between duration of shift work and CHD was stronger in the first half of follow-up than in the second half (P=.02 for interaction), suggesting waning risk after cessation of shift work. Longer time since quitting shift work was associated with decreased CHD risk among ever shift workers in the NHS2 (P<.001 for trend). [table: see text] Among women who worked as registered nurses, longer duration of rotating night shift work was associated with a statistically significant but small absolute increase in CHD risk. Further research is needed to explore whether the association is related to specific work hours and individual characteristics.